Maize Plant Architecture Is Regulated by the Ethylene Biosynthetic Gene ZmACS7. Issue 3 (22nd April 2020) - Li, Hongchao; Wang, Lijing; Liu, Meishan; Dong, Zhaobin; Li, Qifang; Fei, Shulang; Xiang, Hongtu; Liu, Baoshen; Jin, Weiwei
Abstract : Alteration of the C terminus of 1-aminocyclopropane-1-carboxylic acid (ACC) Synthase 7 (ZmACS7), an ethylene biosynthetic protein, enhances the stability of this enzyme, thus increasing ACC and ethylene production, which in turn alters plant architecture in maize. Abstract: Plant height and leaf angle are two crucial determinants of plant architecture in maize ( Zea mays ) and are closely related to lodging resistance and canopy photosynthesis at high planting density. These two traits are primarily regulated by several phytohormones. However, the mechanism of ethylene in regulating plant architecture in maize, especially plant height and leaf angle, is unclear. Here, we characterized a maize mutant, Semidwarf3 ( Sdw3 ), which exhibits shorter stature and larger leaf angle than the wild type. Histological analysis showed that inhibition of longitudinal cell elongation in the internode and promotion in the auricle were mainly responsible for reduced plant height and enlarged leaf angle in the Sdw3 mutant. Through positional cloning, we identified a transposon insertion in the candidate gene ZmACS7, encoding 1-aminocyclopropane-1-carboxylic acid (ACC) Synthase 7 in ethylene biosynthesis of maize. The transposon alters the C terminus of ZmACS7. Transgenic analysis confirmed that the mutant ZmACS7 gene confers the phenotypes of the Sdw3 mutant. Enzyme activity and protein degradation assays indicated that the altered C terminus of ZmACS7 in the Sdw3 mutant increases this protein's stability but does not affect its catalytic activity. The ACC and ethylene contents are dramatically elevated in the Sdw3 mutant, leading to reduced plant height and increased leaf angle. In addition, we demonstrated that ZmACS7 plays crucial roles in root development, flowering time, and leaf number, indicating that ZmACS7 is an important gene with pleiotropic effects during maize growth and development.